Theoretical framework for the control and guidance of hospital logistics performance management during covid pandemic 19 - MILOU , Karim; TOUATE , Samira (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The purpose of this paper is to try, through a theoretical study, to highlight the main theoretical frameworks of inspiration of the research in management control and the piloting of the hospital logistics performance in the era of the current context characterized by the economic and financial repercussions of the Covid 19 pandemic, and the great tendency of the hospital establishments towards the adoption and the integration of the tools of management control as an inescapable means of piloting the hospital logistics performance. The literature shows a diversity of approaches and currents in logistics performance control. Thus, the expected results stipulate that a great deal of research in management control and hospital logistics performance refers to the resource theory, the stakeholder theory, the network theory, the contingency theory, the systemic approach, Simons' theory and the neo-institutional theory. These theories are fundamental references for understanding the determinants, evolutions and even reconfigurations of management control tools within the hospital supply chain. The results of our study confirmed the contributions of the theory of resources, stakeholders and networks to the adoption and consideration of dimensions other than financial and economic performance by healthcare institutions.